Genetics: finding genes for schizophrenia. - Flint, J; Munafò, MR (Cell Press, 2014)
New studies have substantially advanced our understanding of the genetic architecture of schizophrenia, but we are far from identifying the underlying mutations. We may require new approaches to understand the biological implications of insights into the genetics of psychiatric disease.